2003
DOI: 10.1007/s00259-002-1008-x
|View full text |Cite
|
Sign up to set email alerts
|

Multitracer study with positron emission tomography in Creutzfeldt-Jakob disease

Abstract: During the period February 1997 to April 2000, 15 patients with clinical symptoms of Creutzfeldt-Jakob disease (CJD) were referred to Uppsala University PET Centre. Positron emission tomography (PET) was performed to detect characteristic signs of the disease, e.g. neuronal death and/or astrocytosis in the brain. The examinations were performed in one session starting with oxygen-15 labelled water scan to measure regional cerebral blood flow, followed by imaging with the monoamine oxidase B inhibitor N-[(11)C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(23 citation statements)
references
References 34 publications
(38 reference statements)
2
21
0
Order By: Relevance
“…Recent PET studies reported significant increase in DED binding in patients with moderate to severe AD compared with healthy control subjects [1]. Similar results were reported in other neurodegenerative disorders such as ALS [26] and Creutzfeldt-Jakob disease [27]. These findings suggest that in vivo imaging of activated astrocytes is a promising additional tool useful to assess prognosis and monitoring disease activity and treatment.…”
Section: Monoamine Oxidasesupporting
confidence: 69%
“…Recent PET studies reported significant increase in DED binding in patients with moderate to severe AD compared with healthy control subjects [1]. Similar results were reported in other neurodegenerative disorders such as ALS [26] and Creutzfeldt-Jakob disease [27]. These findings suggest that in vivo imaging of activated astrocytes is a promising additional tool useful to assess prognosis and monitoring disease activity and treatment.…”
Section: Monoamine Oxidasesupporting
confidence: 69%
“…One study in 2002 with fluorodeoxyglucose (FDG) as a tracer found hypometabolism primarily in the parietal region 17 . Another study with FDG also found hypometabolism in the temporal and parietal regions, and the cerebellum 18 . However, each of these studies involved only 5 definite CJD cases.…”
Section: Introductionmentioning
confidence: 89%
“…This molecule is an irreversible MAO-B inhibitor with high affinity and specificity for this enzyme, predominantly expressed on the outer mitochondrial membrane of astrocytes [39]. Thus far, PET studies using 11 C-DED have been performed in some neurological diseases including amyotrophic lateral sclerosis, Creutzfeldt-Jakob disease [67,68,69] and AD [13,14,15,16]. …”
Section: Pet Molecular Imaging Of Neuroinflammationmentioning
confidence: 99%